Two stage robust planning of park integrated energy system considering low carbon - Chen, Shuting; Su, Wanhua; Wu, Binyang (Frontiers in Ecology and Evolution, 2023)
The development of integrated energy systems is a significant way of improving energy efficiency and encouraging renewable energy absorption. However, the uncertainty of renewable energy and loads raise severe challenges to integrated energy system planning. Besides, under the low carbon background, the relationship between reducing carbon emissions and increasing the absorption of renewable energy are not investigated clearly in the planning of the park integrated energy system. Thus, this paper provides a two-stage robust planning method with min-max-min structure to minimize the investment and operation cost of park integrated energy system under the uncertainty of renewable energy and loads. The carbon emission limits and renewable energy penetration constraints are considered in the model. The model is translated into an equal max single-layer model by the Karush Kuhn-Tucker condition and solved based on the column constraint generation algorithm. Case study shows the ability and cost of the park integrated energy system to promote low-carbon emission reduction and renewable energy consumption. Moreover, it proves that although there is some synergy between the low carbon target and the renewable energy consumption target, maximum renewable energy consumption does not mean minimum carbon emissions, and vice versa, and in some cases increasing renewable energy penetration does not necessarily reduce carbon emissions.